Cavernicola pilosa barber, 1937 (Hemiptera, reduviidae, triatominae): First record in amazonas state, brazil - Do Nascimento, Eudi Bonfim; Souza, Éder Dos Santos [UNESP]; de Paiva, Vinícius Fernandes; Chagas, Érica Cristina da Silva; Galvão, Cleber (Pensoft Publishers, 2020)
Cavernicola pilosa Barber, 1937 is a wild triatomine species that generally lives in caves but has been found invading dwellings. It feeds mostly on bat blood. This vector has a wide geographical distribution throughout Central and South America, including Brazil, Ecuador, Colombia, French Guiana, Panamá, Peru, and Venezuela. In Brazil, C. pilosa occurs in the states of Bahia, Pará, Tocantins, Espírito Santo, Goiás, Mato Grosso do Sul, Minas Gerais, Paraná, and Maranhão. We report for the first time its presence in Amazonas state, Brazil.
Keywords: Chagas disease; Triatomines; Tribe Cavernicolini